Standardization of Minimally Invasive Tissue Sampling Specimen Collection and Pathology Training for the Child Health and Mortality Prevention Surveillance Network - Rakislova, Natalia (Clin Infect Dis, 2019)
BACKGROUND: Minimally invasive tissue sampling (MITS) is a simplified postmortem examination technique that has shown to be an adequate approach for cause of death investigation in low-resource settings. It requires relatively low level of infrastructures and can be performed by health professionals with no background in pathology. A training program has been developed for the Child Health and Mortality Prevention Surveillance (CHAMPS) network to guarantee standardization of specimen collection techniques, procedures, and laboratory methods. METHODS: The training program has included assessment of the site capacities and training on a standardized protocol of MITS sampling and histological processing. The project has also introduced a program of training for trainers for the personnel from Mozambique. To guarantee the adequacy of the procedure in each site, a trainer accompanied the local teams when the activities started. Training outcomes were assessed by evaluating the quality of the samples obtained and the quality of the slides produced locally. RESULTS: Between June 2016 and October 2018, the laboratories of 7 sites (Bangladesh, Ethiopia, Kenya, Mali, Mozambique, Sierra Leone, and South Africa) have been evaluated and upgraded. Training has been delivered to 63 staff members from all sites. More than 600 MITS procedures have been performed. The quantity of tissue obtained in the MITS by the local teams was sufficient or abundant in 73%, and 87% of the slides were considered as technically acceptable or excellent. CONCLUSIONS: Satisfactory standardization of MITS and histology procedures has been achieved across all CHAMPS sites through organized capacity-building plans.